How Real-Time Interactivity Influences Impulse Buying Behaviour in Generation Z’s During Live Streaming Shopping: The Mediating Role of Perceived Enjoyment - Indriastuti Herning; Hidayati Tetra; Asnawati; Martiyanti Dwi; Ayu Astried Rusty Febri; Putit Lennora (ECONOMICS)
Live streaming is a new experience for customers to make online purchases because it is real-time, this has led to a surge in live shopping in e-commerce. The purpose of this study investigates the impulsive shopping behavior of Generation Z during live streaming, which is influenced by real-time interaction variables and bridged by stimulus, cognitive and emotional pleasure. The research method used a purposive sampling technique to collect 119 participants through an online survey. Data analysis was carried out using Smart-PLS software. The test results in this study state that real-time interactivity has a positive and significant effect on perceived enjoyment felt by consumers when watching live streaming shopping and perceived enjoyment has a positive - significant effect on consumer impulse buying behavior when live streaming. The indirect finding of the perceived enjoyment variable can bridge the gap in the relationship between real-time interactivity and impulse buying behavior. The contribution of this research provides an understanding of the impulsive buying behavior of the live-streaming shopping domain by increasing the interesting interaction through Stimulus Organism Response Theory. Business implications could focus on improving the quality of real-time interactions and promoting limited-time live-streaming intent using live streaming e-commerce platforms.